Hubungan Antara Tingkat Pendidikan Masyarakat Terhadap Literasi Tentang Wakaf Tunai Dan Keputusan Untuk Berwakaf Tunai Di Daerah Istimewa Yogyakarta - Aiyubbi, Dityawarman El; Wijayanti, Diana; Trisanty, Aidha (STIE Ekuitas, 2022)
This research aims to know the relationship between the level of public education on literacy about cash waqf and the decision to cash waqf. The method used in this study is a quantitative research method, with 138 respondents. The analysis technique used in this study was carried out using descriptive statistical data analysis techniques (path analysis). This study's results indicate a direct positive effect between education level on the decision to cash waqf and a positive indirect effect between education level on the decision to cash waqf with the literacy variable for cash waqf as an intervening variable.